استخدام البرنامج هيلو توك Hello Talk بطريقة التعلم القائم على المشروع "الأصدقاء العرب" لترقية مهارة الكلام في مركز الأزهر لتعليم اللغة العربية للناطقين بغيرها بباري كديري - Izza R.U, Nafisatul; Kusumadewi, Novita (International Conference on Humanity Education and Society (ICHES), 2024)
This study aims to describe the application of the project based learning method "Arab Friends" through the use of the HelloTalk application to improve Arabic speaking skills. The method used is a qualitative descriptive method with a primary data collection process through observation, interviews, and document review. The subjects of the study were 25 middle-level students at the Al Azhar Arabic Course. The results of data analysis show that (1) This research was successfully applied through several stages of implementation, namely preparing project questions or assignments, designing project plans, preparing schedules and monitoring student project progress, test results and experience evaluation. (2) Based on the previous stage, the "Arab Friends" project-based learning method through the use of the Hello Talk program has been successfully applied so that it can improve students' speaking skills as evidenced by the form of the "Friends of the Arabs" project report along with a record of conversations that have been carried out.